2021
DOI: 10.3847/2041-8213/abfaa3
|View full text |Cite
|
Sign up to set email alerts
|

The Tarda Meteorite: A Window into the Formation of D-type Asteroids

Abstract: Dynamic models of solar system evolution suggest that D-type asteroids formed beyond Saturn's orbit and represent invaluable witnesses of the prevailing conditions in the outer solar system. Here, we report a comprehensive petrographic and isotopic characterization of the carbonaceous chondrite Tarda, a recent fall recovered in the Moroccan Sahara. We show that Tarda shares strong similarities with the D-type-derived chondrite Tagish Lake, implying that Tarda represents a rare sample of D-type asteroids. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 46 publications
5
25
1
Order By: Relevance
“…In addition, both chondrites show similar cosmic-ray exposure and radiogenic retention ages: 5-10 Ma and 2.4-2.7 Ga for Tarda, and 5-8 Ma and 2.0-2.8 Ga for Tagish Lake. Altogether, our results thus reinforce the genetic link between Tarda and Tagish Lake, which share similar isotopic signatures for elements having drastically different geochemical behaviour (Marrocchi et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In addition, both chondrites show similar cosmic-ray exposure and radiogenic retention ages: 5-10 Ma and 2.4-2.7 Ga for Tarda, and 5-8 Ma and 2.0-2.8 Ga for Tagish Lake. Altogether, our results thus reinforce the genetic link between Tarda and Tagish Lake, which share similar isotopic signatures for elements having drastically different geochemical behaviour (Marrocchi et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…Based on multiple isotopic systems (i.e. H, C, N and O), it has recently been proposed that Tarda and Tagish Lake could be genetically related (Marrocchi et al, 2021). This hypothesis can be tested in the light of noble gas measurements reported here.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…3). Tarda has been proposed to derive from D-type asteroids with higher ice proportion than Ctype asteroids (Marrocchi et al, 2021) while CIs have shown resemblance to the Cb-asteroid Ryugu samples recovered during the Hayabusa2 mission (Watanabe et al, 2017). In both cases, the parent bodies originate from distant regions, possibly outside the CO 2 and H 2 O snowlines in the case of the Ryugu parent asteroid (Nakamura et al, 2022), whilst CI Orgueil possesses a volatile content of cometary origin (Gounelle and Zolenski, 2014).…”
Section: Aqueous Alteration Vs Asteroidal Source; Influence On the Or...mentioning
confidence: 99%
“…They may have slight concave curvature or be relatively flat. Tagish Lake was the earliest meteorite spectral match in the literature Barucci et al 2018), although they have also more recently been associated with the Tarda carbonaceous chondrite (Marrocchi et al 2021) and a primitive clast from the Zag ordinary chondrite meteorite (Kebukawa et al 2019). While the study of Tarda measures compositional similarity to the expected composition of D-types, it does not present data to prove spectral similarity.…”
Section: D-typesmentioning
confidence: 99%